The magnetic inorganic-organic hybrid membranes based on polyimide matrices for gas separation. (1st February 2017) - Rybak, Aleksandra; Rybak, Aurelia; Kaszuwara, Waldemar; Awietjan, Stefan; Molak, Rafał; Sysel, Petr; Grzywna, Zbigniew J.
Abstract: Various magnetic inorganic-organic hybrid membranes based on linear or hyperbranched polyimide matrix and magnetic microparticles were prepared and characterized. It was stated that the magnetic membrane's gas transport parameters ( D, P, S and α) were improved with the rise of membrane's saturation magnetization, remanence, magnetic particle content and coercivity, associated with the decrease in magnetic powder particle size. The hybrid membranes had much higher gas permeability and diffusivity, while their permselectivity and solubility coefficient values slightly increased. The mechanical and rheological parameters of the tested membranes were improved by the increase of the magnetic filler addition, decrease of its granulation and selection of appropriate type of polymer matrix. The best resistance to elastic deformation had the hybrid PI membranes with high filler addition and small granulation, while their resistance to viscous flow increased with filler particle size rise. The investigated membranes showed the excellent thermooxidative stability.